Teamwork in nursing: restricted to nursing professionals or an interprofessional collaboration? - Geisa Colebrusco de Souza; Marina Peduzzi; Jaqueline Alcântara Marcelino da Silva; Brígida Gimenez Carvalho
Abstract OBJECTIVE To understand the nursing professionals' conceptions of teamwork and their elements. METHOD A qualitative study conducted in an oncological hospital using a semi-structured interview with 21 nursing professionals. RESULTS Two conceptions emerged from the accounts: teamwork restricted to nursing professionals and teamwork with interprofessional collaboration with particular importance for interactive dimensions: communication, trust and professional bonds, mutual respect and recognition of the other's work, collaboration, and conflict, with this last subcategory considered as an obstacle to teamwork. CONCLUSION Nursing conceives teamwork as an interprofessional practice, which is a result of the quality of interaction among professionals from different areas and involves the recognition and handling of conflicts.